2022
DOI: 10.1097/cce.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Perspective of Awake Proning: A Cross-Sectional Interview-Based Survey From COVID-19–Recovered Patients

Abstract: IMPORTANCE AND OBJECTIVES: To assess the knowledge, attitude, and practice of the patients who underwent prone positioning during their COVID-19 illness in the hospital. DESIGN: Cross-sectional study. SETTING: Aga Khan University Hospital, Karachi, Pakistan. PARTICIPANTS: COVID-19–recovered patients. INTERVENTIONS: No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…This obstacle may be addressed through strategies such as using additional pillows or rolled towels [ 18 ], and the adoption of novel positions like the dolphin prone position [ 31 ], Reverse Trendelenburg position [ 11 ], alternating prone positioning [ 32 ], and Rodin’s position [ 33 ]. Our study also found that the lack of knowledge and misconceptions about prone position were major factors affecting patients’ psychological capability, which may be related to their limited ability to understand and accept information, similar to the survey by Sethi et al [ 19 ]. Moreover, these factors may also lead to patients’ fear of prone position ventilation, thereby weakening their confidence in adhering to the prescribed course of action.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This obstacle may be addressed through strategies such as using additional pillows or rolled towels [ 18 ], and the adoption of novel positions like the dolphin prone position [ 31 ], Reverse Trendelenburg position [ 11 ], alternating prone positioning [ 32 ], and Rodin’s position [ 33 ]. Our study also found that the lack of knowledge and misconceptions about prone position were major factors affecting patients’ psychological capability, which may be related to their limited ability to understand and accept information, similar to the survey by Sethi et al [ 19 ]. Moreover, these factors may also lead to patients’ fear of prone position ventilation, thereby weakening their confidence in adhering to the prescribed course of action.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, the study found a new result that daily habits had both positive and negative effects on adherence. Those who prefer to sleep on their stomach can last longer in treatment, but for others, it can be a difficult posture to maintain and an uneasy maneuver to perform [ 19 ]. Notably, participants with higher compliance reported an increased tolerance for the prone position over time, suggesting that healthcare professionals could encourage patients to gradually increase the duration of each session and try the prone position several times throughout the day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More severely ill patients are more likely to be cared for in settings with greater access to staff for support in turning and maintaining APP, whereas patients with lower oxygen requirements, cared for in less intensive environments, are more able to move themselves to a position of their choice. Studies in the UK, Pakistan and China which have examined acceptability from patient perspectives suggest overall negative attitudes to APP related to discomfort, physical consequences and social factors which may influence patients’ willingness to self-prone (15–17). Concurrent patient perspectives from randomised controlled trials remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Despite prone position that been combined with oxygen therapy can physiologically improve pulmonary function, this position is not very comfortable for the patients because they have to lie on their stomachs for a while when the oxygen therapy and other monitoring devices are still attached 6 . Furthermore, some patients move their bodies to be more comfortable, and it was far from the standard of prone position form.…”
Section: Introductionmentioning
confidence: 99%